COMPONENTES QUE DETERMINAN LA DESERCIÓN (Journal on studies and research of academic knowledge, 2017)
The research is conducted by the need to know the background of the collegedropout in the Faculty of Sciences and Technology, following this, the general objective of analyzing the components that determine the dropout students of the Faculty of Sciences and Technology of the National University of Itapúa periods in the years 2010 to 2013. Due to its characterístics, design research is not experimental, exploratory type, quantitative approach. The most significant results show that the dropout rate as the one given in greater measure is the initial (in the first half) and institutional (students attend other educational institutions). As for the causes of desertion shows that one of the main reasons for dropping out is working, this results in failure to attend classes and low student commitment to education and irreversible backwardness, and another reason is disinformation students on graduate profile and employment career field. Regarding retention mechanisms, the institution takes few actions to prevent students from dropping his college career.
Keywords: College dropout; Type; Cause; Retention